1998
DOI: 10.1073/pnas.95.19.11059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of bacterial adhesion monitored by atomic force microscopy

Abstract: Bacterial adhesion and the subsequent formation of biofilm are major concerns in biotechnology and medicine. The initial step in bacterial adhesion is the interaction of cells with a surface, a process governed by long-range forces, primarily van der Waals and electrostatic interactions. The precise manner in which the force of interaction is affected by cell surface components and by the physiochemical properties of materials is not well understood. Here, we show that atomic force microscopy can be used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
269
4
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 347 publications
(282 citation statements)
references
References 45 publications
7
269
4
2
Order By: Relevance
“…Electrostatic interactions between the negatively charged bacterial surface (29) and substrates 1 and 2 ( Fig. 2) were exploited to capture the fluorescent and positively charged products of the enzymatic cleavage reaction on the surface of the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic interactions between the negatively charged bacterial surface (29) and substrates 1 and 2 ( Fig. 2) were exploited to capture the fluorescent and positively charged products of the enzymatic cleavage reaction on the surface of the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…It allows the use of almost any substrate, but raises the issue of how to stably attach cells to an AFM cantilever. First attempts in this direction were made by Razatos et al [980] who demonstrated that it is possible to coat silicon nitride AFM cantilevers including the tip with a layer of E. coli cells, if the cells were fixed by glutaraldehyde treatment. The authors took advantage of such functionalized tips to study the adhesion of E. coli [386,981] (see also Ref.…”
Section: Cell Probe Measurementsmentioning
confidence: 99%
“…A resolution of 2 nm has been reached using LiCl treatment to chemically fix Lactobacillus helveticus [15]. Although pre-treatment improves the image resolution, there is a question as to whether fixation procedures interfere with the force measurements as has been shown previously [30][31][32]. To provide realistic global force measurements on viable biofilms, wet mode experiments were employed in this study.…”
Section: Force Characterisationmentioning
confidence: 99%